1990
DOI: 10.1111/j.1600-051x.1990.tb01046.x
|View full text |Cite
|
Sign up to set email alerts
|

Dental health behaviors and periodontal disease indicators in Danish youths

Abstract: The purpose of the present study was to analyse the epidemiologic relationship between dental health behaviors and periodontal disease. Indicators of periodontal disease in terms of bleeding and calculus were measured dichotomously (absence/presence). Periodontal pockets were as follows: normal pockets (0-3 mm), shallow pockets (4-5 mm), and deep pockets (6+ mm). The indicators were measured on 4 surfaces on 6 index teeth (16, 11, 26, 36, 31, 46) in 1984-85. The highest value for each tooth of bleeding (0/1), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
1
1

Year Published

1991
1991
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 5 publications
1
15
1
1
Order By: Relevance
“…One prospective cohort study 83 reported a significant increase in the percentage of bleeding surfaces with an increase in the distribution of dental check frequencies over a 9-year period. One 58 reported no significant relationship between the proportion of gingival units with bleeding and dental check frequency, while a further cross-sectional study 85 reported a significant negative association between bleeding index and dental check frequency.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…One prospective cohort study 83 reported a significant increase in the percentage of bleeding surfaces with an increase in the distribution of dental check frequencies over a 9-year period. One 58 reported no significant relationship between the proportion of gingival units with bleeding and dental check frequency, while a further cross-sectional study 85 reported a significant negative association between bleeding index and dental check frequency.…”
Section: Discussionmentioning
confidence: 99%
“…Three studies 58,83,85 investigating the relationship between dental check frequency and bleeding reported inconsistent findings. One prospective cohort study 83 reported a significant increase in the percentage of bleeding surfaces with an increase in the distribution of dental check frequencies over a 9-year period.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations